Define before you divide: surgical lessons from cystic duct insertion into the right hepatic duct - Thor, Sze Mun; Goai, Xin Yi; Atanasov, Georgi D. (International Surgery Journal, 2026)
Anatomical variations of the cystic duct are uncommon but clinically significant, as unrecognized variants increase the risk of catastrophic bile duct injury during cholecystectomy. We report a case of a 47-year-old woman presenting with biliary colic and transient cholestatic liver enzyme derangement, in whom an aberrant cystic duct draining directly into the right hepatic duct (RHD) was identified intraoperatively during cholangiography. The case highlights operative decision-making and reviews the role of dedicated preoperative imaging in detecting biliary duct anomalies to optimize surgical planning.